Design Rencana Strategi Formulasi dan Implementasi Bisnis pada Barbershop Vax Wijaya di Subang - Sopiawadi, Mutqi; Mutiara, Hatina; Aditya, Maya; Wahab, Kevin (PT. Alahyan Publisher Sukabumi, 2025)
Vax Wijaya Barbershop is one of leading barbershops in Subang City which provides professional haircut services with high quality and affordable prices. With several branches in various areas of Subang Regency, this barbershop is the main choice for people who want a modern and neat hairstyle. Supported by experienced barbers, Vax Wijaya Barbershop offers various haircut styles, from classics to the latest trends, according to customer needs. Apart from haircut services, this barbershop also provides various additional facilities to increase customer comfort, such as washing hair, using warm towels, providing hair vitamins, and styling hair according to the customer’s wishes. Focusing on customer satisfaction makes Barbershop Vax Wijaya continue to innovate in providing the best service.